Comment furent rapatriés les greffes de Saint-Domingue, 1803-1820 - Menier, Marie-Antoinette (Gazette des archives, 1978)
The Section Outre-Mer of the Archives nationales keeps some copies of the archives of the tribunals of Saint-Domingue under the French rule. How these copies came to France is a matter of conjecture. Despite many losses, they are of great interest for the history of French Saint-Domingue, because the archives which were left in the island have been nearly ail destroyed.

Les sources de l’histoire des Antilles dans les Archives nationales françaises - Menier, Marie-Antoinette (Bulletin de la Société d'Histoire de la Guadeloupe, 1978)

Actes notariés et histoire coloniale - Poisson, Jean-Paul (Gazette des archives, 1973)

Les archives de l'expansion française outre-mer conservées en Métropole - Laroche, Charles (dit Carlo) (Gazette des archives, 1966)

Les archives anciennes des Colonies françaises aux Archives nationales - Taillemite, Étienne (Gazette des archives, 1964)

Les archives de la Guyane française - de Font-Réaulx, Jacques (Gazette des archives, 1962)

Les archives de l'Afrique équatoriale française. Lettre de Brazzaville - Glénisson, Jean (Gazette des archives, 1957)

Les archives du Ministère de la France d'Outre-Mer - Laroche, Charles (dit Carlo) (Gazette des archives, 1948)